Effects of cold-water immersion and contrast-water therapy after training in young soccer players - de Nardi, M.; La Torre, A.; Barassi, A.; Ricci, C.; Banfi, G. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM:Recent studies have investigated the importance of recovery strategies after training session, including hydrotherapy and cryotherapy. However, only a few studies have focused on cold-water immersion (CWI) treatments in team sport disciplines. The present study investigates the effects of CWI and contrast-water therapy (CWT) on the performance of young male soccer players during a week of training. METHODS: Eighteen young soccer players participated in the present study (age 15.5±1.0 years, weight 61.8±3.0 Kg, height 175.5±4.0 cm and training experience 8.1±1.0 years). They were involved in a four-day study with recovery using CWI or with CWT after each training session by using performance tests and small-sided games. We measured uric acid concentration, leukocytes, haemoglobin, reticulocytes and creatine kinase changes in the blood, axillary temperature, rating of perceived exertion after a training session, heart rate during exercise, performance tests (counter movement jump, repeated sprint ability and 5` shuttle run). RESULTS:No significant difference were reported between groups when different physiological tests were used; CWI and CWT did not negatively influence the performances of the athletes. The principal effect of CWI was a reduced perception of fatigue after the training session. The use of active recovery protocols based on cold water or cold/thermoneutral water did not induce modifications of inflammatory and haematological markers in young soccer players. CONCLUSION:The beneficial effect of a reduced perception of fatigue can improve training and competitions in young soccer players.